Bioenergy development in Thailand based on the potential estimation from crop residues and livestock manures. (January 2021) - Wang, Wen; Porninta, Kritsadaporn; Aggarangsi, Pruk; Leksawasdi, Noppol; Li, Lianhua; Chen, Xiaoyan; Zhuang, Xinshu; Yuan, Zhenhong; Qi, Wei
Abstract: Bioresource evaluation is prerequisite and important to reduce cost of feedstock collection and avoid battle for feedstock to promote the healthy development of bioenergy industry. This study estimated Thai bioresources from arable field crops, horticultural plants and livestock with product quantity or livestock number, residue-product ratio or manure productivity, and moisture content. Rice straw and husk, para rubber residues and cattle manure separately have the top amount in arable field crop biomass, horticultural residues and livestock manures. The northeastern region has the most amounts of arable field crop biomass and livestock manures, and the southern region possesses the largest quantities of horticultural residues. The available energy potentials from residues of arable field crops and horticultural plants can reach to maximum of 4.91 × 10 5  TJ and 7.65 × 10 5  TJ, respectively, which can theoretically share 21.67% of current total primary energy supply. The available biogas potential from livestock manures is nearly ten times than its current generation. After analysis the status of technologies and government policies for Thai bioenergy industry, it indicates that the utilization of bioenergy in the form of electricity, heat and transportation fuels has promising prospect in Thailand. The provinces of Thailand which are more suitable for developing bioenergy industry are suggested. This work may guide the reasonable layout of bioenergy industry in Thailand via the presence of bioresouces distribution in every province. Highlights: Rice straw and husk are the most abundant field crops' biomass in Thailand. Residues of para rubber has largest amount among Thai horticultural plants. Cattle excretes more manure than other livestock in Thailand. Northeastern region of Thailand is an optimal place to develop various bioenergies. Thailand has huge bioresources potential and prospect to develop bioenergy industry.